PENERAPAN JURNALISTIK TELEVISI PADA PROGRAM SCHOOL UPDATE DI RIAU TELEVISI - Vika Gusria Putri; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
School update program is the only Riau Television progam which its production procces done by students. School update program present as a medium of creativity learning and development of Pekanbaru Senior High School in term of early television journalism implementation to create a young and high quality journalist. The implementation of this television journalism done through basic television journalism training program and practice on the field. The aim of this research is to determine how is the implementation of basic television journalism dan reporting process at school update program.This research uses descriptive analysis and qualitative approach, conducted in Riau Televisi at Jalan H.R Soebrantas Km 10,5 Pekanbaru. Sampling technique are: observation, interview and documentation. Through sampling purposive, the number of subjects in this research are six person consisting of one producer as a key informant and five persons as a school update member. Data were analized using analysis model of Miles and Huberman interactive data.The result of this research indicates several things: first, the implementation of television journalism for school update program in Riau Television done through a series of basic television journalism training and practice on the field. These training are: the mastery of 5W+1H formula, news source, news value, and news writing. Second, reporting process in school update program which contain search activities and collection of news materials, and news editing activities up until showtime. According to students report from the field, that in the search process and news materials collecting, the students are able to fullfil 5W+1H formula, identify news source and conceive the news value. From the student narrative and visual, they able to show an increase skill when doing interview and taking pictures even though its still need improvement. In news processing, students are able to apply inverted pyramid news writing standards. Although its bit different with the writing and television news format in common. School update program tend to citizen journalism. At the edting process, editor school update uses editing non linear technique. Problems encountered in the overal process of editing found in the lack of visual.Keyword: Implementation, Television Journalism, Program